2016
DOI: 10.1073/pnas.1509184113
|View full text |Cite|
|
Sign up to set email alerts
|

Dominant hemisphere lateralization of cortical parasympathetic control as revealed by frontotemporal dementia

Abstract: The brain continuously influences and perceives the physiological condition of the body. Related cortical representations have been proposed to shape emotional experience and guide behavior. Although previous studies have identified brain regions recruited during autonomic processing, neurological lesion studies have yet to delineate the regions critical for maintaining autonomic outflow. Even greater controversy surrounds hemispheric lateralization along the parasympathetic–sympathetic axis. The behavioral va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 96 publications
10
79
1
Order By: Relevance
“…The subjective experience of emotion is likely to be integral to the internalization of observed emotional states in others during emotional contagion. Our findings therefore provide a candidate neurobiological mechanism for the blunted emotional reactions and loss of empathy that characterize FTD syndromes38, 39 and amplify previous work linking altered cardiac vagal tone to reduced agreeableness in bvFTD 24. Impaired awareness of heartbeat has also previously been demonstrated in FTD25, 32: taken together with the present findings, this suggests that induction, awareness, and cognitive decoding of embodied emotional responses all contribute to emotional responsiveness and may be separably targeted in FTD syndromes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The subjective experience of emotion is likely to be integral to the internalization of observed emotional states in others during emotional contagion. Our findings therefore provide a candidate neurobiological mechanism for the blunted emotional reactions and loss of empathy that characterize FTD syndromes38, 39 and amplify previous work linking altered cardiac vagal tone to reduced agreeableness in bvFTD 24. Impaired awareness of heartbeat has also previously been demonstrated in FTD25, 32: taken together with the present findings, this suggests that induction, awareness, and cognitive decoding of embodied emotional responses all contribute to emotional responsiveness and may be separably targeted in FTD syndromes.…”
Section: Discussionsupporting
confidence: 88%
“…We hypothesized that cardiac modulation would be attenuated in bvFTD and nfvPPA due to degeneration of fronto‐insular networks in these diseases, but relatively preserved (and separable from emotion identification) in syndromes targeting the anterior temporal lobes (svPPA and rtvFTD) 18, 20, 21. We further hypothesized that emotion recognition ability but not cardiac reactivity would be associated with semantic knowledge, while cardiac reactivity would correlate with atrophy in components of the central autonomic regulatory network (ACC, insula, OFC) 15, 16, 24…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…28 The paucity of differences in any of the conventional inflammatory outcome measures may be explained by the recent findings, which suggest that the cortical atrophy, and specifically cortical hemispheric volume loss lateralization, could influence the homeostasis of autonomic nervous system (ANS). 29 For example, autonomic mechanisms related to cardiovascular control are located in the neuronal circuitry of the insular cortex, dorsal anterior cingulate, prefrontal cortex, and hippocampus. 30 It has been reported that dysregulation of the ANS is associated with variability of the heart rate, and fluctuations of the blood pressure, all of which can contribute to reaching a critical closing pressure that leads to the collapse of the cerebral venous system.…”
Section: Discussionmentioning
confidence: 99%
“…[75][76][77] Indeed, disturbances in this left-right balance may yield the pattern of autonomic disturbances often seen in frontotemporal dementia. 78 In this light, bilateral disturbances speak to a 'balanced' interoceptive and autonomic dysregulation in those at HR of BD.…”
Section: Discussionmentioning
confidence: 99%